Developing professional iPhone photography : using Photoshop, Lightroom, and other iOS and desktop apps to create and edit photos /: using Photoshop, Lightroom, and other iOS and desktop apps to create and edit photos. ([2018]) - Elmansy, Rafiq
No abstract available